The genus Doloploca Hübner (Lepidoptera: Tortricidae: Tortricinae) new to Korea with two new records - Hye-Min Byun; UnHong Heo; Youngwoo Nam; Jong-Kook Jung; Sunghoon Jung (Journal of Asia-Pacific Biodiversity, 2022)
The genus Doloploca Hübner (Lepidoptera: Tortricidae: Tortricinae) is reported for the first time from Korea with two newly recorded species: Doloploca praeviella (Erschoff, 1877) and D. buraetica Staudinger, 1892. Descriptions and illustrations of adults, including the wing pattern and genitalic structures, and brief biological information are provided.